Effects of manipulating ball type on youth footballers` performance during small-sided games - Santos, S.; Coutinho, D.; Gonçalves, B.; Abade, E.; Pasquarelli, B.; Sampaio, J. (Pediatric Exercise Science, 2020)
This study aimed to identify the effects of manipulating the ball type in players` physical, technical, creative and tactical performance in two small-sided games situations: 4-a-side and 6-a-side. There were four conditions: (i) Football, using regular football ball; (ii) Handball, using handball ball; (iii) Rugby, playing with rugby ball, and (d) Mixed, at every 2 min the ball type was randomly changed. Players` technical and creative actions were analysed through notational analysis, while GPS positional data were used to process the physical and tactical variables. During the 4-a-side, the rugby and mixed conditions induced more effects. From the physical perspective, there were moderate decreases in the total distance covered (-11.1%; ±3.1% and -6.2; ±3.6) and distance covered while jogging (-11.9%; ±3.6% and -8.0; ±3.9) in both scenarios, respectively. In tactics, there were small to moderate decreases in both conditions in the distance between team`s centroids (-5.5; ±6.0 and -6.8%; ±5.1%) and effective playing space (-16.2; ±9.8 and -20.6; ±12.3), respectively. In turn, all variables were affected by the ball type modification during the 6-a-side compared to the Football balls. Modifying the type of ball promoted small to moderate decreases in the number of successful passes and dribbles, in the fluency and versatility, as well as in most of the physical variables. Additionally, changing the ball type has also affected (small decreases) in the regularity in the distance between teams. Coaches may promote variability in the training tasks using different balls to develop the players` adaptive movement behaviours.